Understanding Structure–Property Relationships of MoO3‑Promoted Rh Catalysts for Syngas Conversion to Alcohols - Asundi, Arun S; Hoffman, Adam S; Bothra, Pallavi; Boubnov, Alexey; Vila, Fernando D; Yang, Nuoya; Singh, Joseph A; Zeng, Li; Raiford, James A; Abild-Pedersen, Frank; Bare, Simon R; Bent, Stacey F (Journal of the American Chemical Society, 2019)
Rh-based catalysts have shown promise for the direct conversion of syngas to higher oxygenates. Although improvements in higher oxygenate yield have been achieved by combining Rh with metal oxide promoters, details of the structure of the promoted catalyst and the role of the promoter in enhancing catalytic performance are not well understood. In this work, we show that MoO3-promoted Rh nanoparticles form a novel catalyst structure in which Mo substitutes into the Rh surface, leading to both a 66-fold increase in turnover frequency and an enhancement in oxygenate yield. By applying a combination of atomically controlled synthesis, in situ characterization, and theoretical calculations, we gain an understanding of the promoter-Rh interactions that govern catalytic performance for MoO3-promoted Rh. We use atomic layer deposition to modify Rh nanoparticles with monolayer-precise amounts of MoO3, with a high degree of control over the structure of the catalyst. Through in situ X-ray absorption spectroscopy, we find that the atomic structure of the catalytic surface under reaction conditions consists of Mo–OH species substituted into the surface of the Rh nanoparticles. Using density functional theory calculations, we identify two roles of MoO3: first, the presence of Mo–OH in the catalyst surface enhances CO dissociation and also stabilizes a methanol synthesis pathway not present in the unpromoted catalyst; and second, hydrogen spillover from Mo–OH sites to adsorbed species on the Rh surface enhances hydrogenation rates of reaction intermediates.